Studying literacy as situated social practice : the application and development of a research orientation for purposes of addressing educational and social issues in South African contexts - Prinsloo, Mastin (Social Anthropology, 2016)
This is a study of the application in South Africa of a social practices approach to the study of literacy. A social practices approach conceptualizes literacy practices as variable practices which link people, linguistic resources, media objects, and strategies for meaning-making in contextualized ways. These literacy practices are seen as varying across broad social contexts, and across social domains within these contexts, and they can be studied ethnographically. I examine how this approach is applied across four critical themes of study in South Africa, namely: the uses and valuations of reading and writing by adults without schooling; the historical circumstances whereby literacy comes to be identified as a resource of European culture in colonial South Africa; children's early engagement with literacy informal and informal contexts; and reading and writing in relation to electronic and digital media. I review examples of ethnographic research in each case, in which I have participated as a researcher, and examine how the approach has been applied, tested and modified in each case of its application. The research in each case showed literacy's incorporation in complex and variable ways in situated, located human activities. Whereas the first application of the social practices approach, that of the SoUL project detailed how literacy operated as everyday practice amongst people with little or no schooling, the research lacked a theoretical perspective to explain how these practices came to take the form and status that they did, as regards the influences upon them from outside the immediate settings that were studied. Over the subsequent studies I developed a revised approach to the study of literacy which detailed the explanatory usefulness of studying how literacy practices that network across larger domains than the local have effect on the construction of local practices, in both historical as well as contemporary examples. Literacy practices were not simply the products of local activity but involved rather the particular local application of communication technologies, language and artefacts that originated from outside the immediate social space. However, local applications involved original, indeterminate and varied uses of those resources. Includes bibliographical references (p. 203-223).